The perceptions of users regarding multimedia principles in mobile-based Japanese language learning - Mohammad Ayub, Mohd Sofi; Talib, Othman; Siew, Nyet Moi (Sakarya Universitesi, 2018)
This study aimed to explore the perceptions of users regarding the use of seven multimedia principles in mobile-based Japanese language learning. Students and lecturers expounded their views on these seven multimedia principles: Generative Learning, Spatial Contiguity, Temporal Contiguity, Coherence, Modality, Redundancy and Personalization. A single group with intervening mobile-based Japanese language learning design was used to test each of the multimedia principles. The participants consisted of 62 undergraduates and three Multimedia lecturers. A mixed method approach was employed where questionnaires and interviews were used as data collection tools. The findings revealed that a majority of the respondents agreed that the multimedia principles were appropriate for application in mobile-based Japanese language learning, except for the Personalization and Redundancy principles. The respondents expressed the need for incorporating on-screen text and formal style text in a mobile learning environment. The findings of this study can facilitate instructors and developers to develop an optimal mobile-based learning experience for Japanese language learners.